Characteristics and outcomes of patients with acute myeloid leukemia admitted to intensive care unit with acute respiratory failure: a post-hoc analysis of a prospective multicenter study - Carolina Secreto; Dara Chean; Andry van de Louw; Achille Kouatchet; Philippe Bauer; Marco Cerrano; Etienne Lengliné; Colombe Saillard; Laurent Chow-Chine; Anders Perner; Peter Pickkers; Marcio Soares; et al. (Annals of Intensive Care, 2023)
Abstract Background Acute respiratory failure (ARF) is the leading cause of intensive care unit (ICU) admission in patients with Acute Myeloid Leukemia (AML) and data on prognostic factors affecting short-term outcome are needed. Methods This is a post-hoc analysis of a multicenter, international prospective cohort study on immunocompromised patients with ARF admitted to ICU. We evaluated hospital mortality and associated risk factors in patients with AML and ARF; secondly, we aimed to define specific subgroups within our study population through a cluster analysis. Results Overall, 201 of 1611 immunocompromised patients with ARF had AML and were included in the analysis. Hospital mortality was 46.8%. Variables independently associated with mortality were ECOG performance status ≥ 2 (OR = 2.79, p = 0.04), cough (OR = 2.94, p = 0.034), use of vasopressors (OR = 2.79, p = 0.044), leukemia-specific pulmonary involvement [namely leukostasis, pulmonary infiltration by blasts or acute lysis pneumopathy (OR = 4.76, p = 0.011)] and liver SOFA score (OR = 1.85, p = 0.014). Focal alveolar chest X-ray pattern was associated with survival (OR = 0.13, p = 0.001). We identified 3 clusters, that we named on the basis of the most frequently clinical, biological and radiological features found in each cluster: a “leukemic cluster”, with high-risk AML patients with isolated, milder ARF; a “pulmonary cluster”, consisting of symptomatic, highly oxygen-requiring, severe ARF with diffuse radiological findings in heavily immunocompromised patients; a clinical “inflammatory cluster”, including patients with multi-organ failures in addition to ARF. When included in the multivariate analysis, cluster 2 and 3 were independently associated with hospital mortality. Conclusions Among AML patients with ARF, factors associated with a worse outcome are related to patient’s background (performance status, leukemic pulmonary involvement), symptoms, radiological findings, the need for vasopressors and the liver SOFA score. We identified three specific ARF syndromes in AML patients, which showed a prognostic significance and could guide clinicians to optimize management strategies.